Using Fault Injection to Assess Blockchain Systems in Presence of Faulty Smart Contracts - Hajdu, Ákos (2020)
Authors' manuscript. Published in IEEE Access 2020. The final publication is available at IEEE via http://dx.doi.org/10.1109/ACCESS.2020.3032239